Influence of short-term pre-aging in vacuum on physicochemical characteristics and consumer acceptability of modified atmosphere packed beef steaks - Łopacka Joanna; Żontała Katarzyna; Pietras Jacek; Półtorak Andrzej; Wierzbicka Agnieszka (Irish Journal of Agricultural and Food Research, 2015)
The objective of this study was to investigate the physiochemical changes and consumer acceptability of meat packed in high oxygen modified atmosphere during 12 days of storage with and without pre-aging in vacuum for 7 days. Steak samples from forequarter muscles Infraspinatus and Supraspinatus were stored at 2°C and tested for colour, Warner–Bratzler shear force (WBSF), storage/cooking loss, and consumer acceptability. Overall consumer acceptability at the beginning of modified atmosphere display was higher for aged Infraspinatus samples, however at the end of display samples from both treatments were equally rated by consumers. No impact of aging was observed in terms of storage loss, while cooking loss was slightly affected by aging, resulting in higher losses in aged samples at the end of modified atmosphere storage. Inclusion of an aging process prior to modified atmosphere display improved the tenderness of Infraspinatus muscle at the 8th day of display and led to a considerable increase in redness of both muscles.